2013
DOI: 10.7314/apjcp.2013.14.10.6089
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Screening for Targets Regulated by Berberine in Breast Cancer Cells

Abstract: Berberine, a common isoquinoline alkaloid, has been shown to possess anti-cancer activities. However, the underlying molecular mechanisms are still not completely understood. In the current study, we investigated the effects of berberine on cell growth, colony formation, cell cycle distribution, and whether it improved the anticancer efficiency of cisplatin and doxorubicin in human breast cancer estrogen receptor positive (ER+) MCF-7 cells and estrogen receptor negative (ER-) MDA-MB-231 cells. Notably, berberi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Although BBR is regarded as a potential therapeutic drug for breast cancer, a better understanding of genes and cellular pathways regulated by BBR is needed to define the mechanisms of its action in cancer treatment39. A recent study also performed genome-wide expression profiling of BBR-treated human breast cancer cells (MCF-7 and MDA-MB-231 cells) using complementary DNA (cDNA) microarrays40. This study identified that many of the target genes of BBR are involved in regulating the cell cycle and cell migration40, which is comparable to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although BBR is regarded as a potential therapeutic drug for breast cancer, a better understanding of genes and cellular pathways regulated by BBR is needed to define the mechanisms of its action in cancer treatment39. A recent study also performed genome-wide expression profiling of BBR-treated human breast cancer cells (MCF-7 and MDA-MB-231 cells) using complementary DNA (cDNA) microarrays40. This study identified that many of the target genes of BBR are involved in regulating the cell cycle and cell migration40, which is comparable to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Berberis vulgaris is one of these medicinal plants that have various biological properties including anti-proliferative, antimigratory and antioxidant activities (Mahata et al 2011;Wen et al 2013). Previous studies mentioned that the phytochemical constituents of Berberis such as antioxidants and anthocyanins increased its bioactivity and was affected by different extraction procedures or the type of solvents used (Abd Elwahab et al 2013;Annegowda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal properties for all parts of this plant have been reported including antimicrobial, antiemetic, antioxidant and anticancer activities (Wen et al 2013;Končić et al 2010;Abd El-wahab et al 2013). The aim of the present study was to examine and compare the biological in vitro activities (antioxidant, anticancer and apoptotic properties) of alcoholic and aqueous extracts of Berberis fruits in human breast cancer cells, MCF-7 in comparison with the normal human epithelial cells (MCF10-A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai-Hong Li 1,2 , Dong-Fang Wu 1 , Hang Ding 2 , Yang Zhao 3 , Ke-Yuan Zhou 2 *, De-Feng Xu 4 * proliferation of various cancer types via the induction of cell cycle arrest and cellular apoptosis (Mantena et al, 2006;Lin et al, 2007;Kuo et al, 2011;Wen et al, 2013). Furthermore, the application of BH has attracted considerable attention for its use as an anti-metastatic agent, suggesting its use in a variety of advanced cancers (Kim et al, 2008;Ho et al, 2009;Kim et al, 2011;Singh et al, 2011).…”
Section: Berberine Hydrochloride Impact On Physiological Processes Anmentioning
confidence: 99%